High temperature sensitivity of Arctic isoprene emissions explained by sedges - Wang, Hui; Welch, Allison M.; Nagalingam, Sanjeevi; Leong, Christopher; Czimczik, Claudia I.; Tang, Jing; Seco, Roger; Rinnan, Riikka; Vettikkat, Lejish; Schobesberger, Siegfried; Holst, Thomas; Brijesh, Shobhit; et al. (Nature Communications, 2024)
It has been widely reported that isoprene emissions from the Arctic ecosystem have a strong temperature response. Here we identify sedges (Carex spp. and Eriophorum spp.) as key contributors to this high sensitivity using plant chamber experiments. We observe that sedges exhibit a markedly stronger temperature response compared to that of other isoprene emitters and predictions by the widely accepted isoprene emission model, the Model of Emissions of Gases and Aerosols from Nature (MEGAN). MEGAN is able to reproduce eddy-covariance flux observations at three high-latitude sites by integrating our findings. Furthermore, the omission of the strong temperature responses of Arctic isoprene emitters causes a 20% underestimation of isoprene emissions for the high-latitude regions of the Northern Hemisphere during 2000-2009 in the Community Land Model with the MEGAN scheme. We also find that the existing model had underestimated the long-term trend of isoprene emissions from 1960 to 2009 by 55% for the high-latitude regions. H.W., A.W., C.C., and A.G. were supported by the National Science Foundation (NSF) Arctic Natural Sciences (ANS) program award ANS-2041251. R. Sheesley is supported by NSF ANS program award ANS-2041240. K.C.B. was supported by NSF ANS program award ANS-2041250. J.T. is supported by Swedish FORMAS (Forskningsråd för hållbar utveckling) mobility Grant (2016-01580) and Villum Young Investigator (Project no. VIL53048). R. Seco, R.R., J.T., and T.H. were supported by the European Research Council (ERC) under the European Union’s Horizon 2020 research and innovation program (grant agreement No. 771012). R.R. and J.T. also acknowledge the support of The Danish National Research Foundation for activities within the Center for Volatile Interactions (VOLT, DNRF168). R. Seco acknowledges a Ramón y Cajal grant (RYC2020-029216-I) funded by MCIN/AEI/ 10.13039/501100011033 and by “ESF Investing in your future”, and project PID2021-122892NA-I00 funded by MCIN/AEI and by “ERDF A way of making Europe”. IDAEA-CSIC ...